PERIOPERATIVE ANTIBIOTIC PROPHYLAXIS IN UROLOGICAL SURGERY: AN UPDATE SYSTEMATIC REVIEW - Kusumo, Bayu; Fadiyah Mahrunnisa, Inannami (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Perioperative antibiotic prophylaxis (PAP) is provided to avoid local or systemic infections, such as surgical site infections (SSI), urinary tract infections (UTI), or sepsis. However, PAP may not be effective in reducing symptomatic UTI in some procedures, such as extracorporeal shock wave lithotripsy and cystoscopy. The aim: This study aims to determine the effectiveness of perioperative antibiotic prophylaxis in urological surgery. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SAGEPUB, and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 105 articles, whereas the results of our search on SAGEPUB brought up 6 articles, our search on ScienceDirect brought up 129 articles. In the end, we compiled 9 papers, 7 of which came from PubMed, and 2 of which came from ScienceDirect. We included nine research that met the criteria. Conclusion: Perioperative antibiotic prophylaxis (PAP) can lower SSI, UTI, and sepsis incidences in urological surgery. In addition, PAP showed a lower positive blood culture. To minimize side effects and lower the risk of drug-resistant organisms, the use of reasonable PAP is advised.